Development of Digital Pop Up Book Media In PKn Subject to Develop Tolerance Attitudes of Grade V Students of Elementary School Muhammadiyah 18 Medan - Siti Anisah (Berpusi Publishing, 2026)
This research is a type of Research and Development (R&D) development research. Research and development is the process of developing new products, and can also develop existing products and be accountable. In this study, the researcher adopted the 4D development model which includes the definition stage, the design stage, the development stage, and the dissemination stage. This research resulted in a product in the form of a digital pop-up book media on the subject of Civics to foster an attitude of tolerance in fifth-grade elementary school students. This is shown from the validation results by media experts with a percentage of 91%, language experts at 88%, and material experts at 96%. The level of practicality of the Nusantara culture-based picture storybook media developed is included in the very practical category. based on the results of practicality tests by teachers with a percentage of 92% and by students at 93%. These results indicate that the media is easy to use, interesting, and helps students in understanding character values, so it is effective for use in learning activities in grade V of elementary school.